Growth patterns by sex and age among under-5 children from 87 low-income and middle-income countries - Cesar Victora; Janaína Calu Costa; Cauane Blumenberg (BMJ Global Health)
Introduction Although boys tend to be more affected by linear growth faltering than girls, little is known about sex differences across distinct age groups. We aimed to compare sex differences in linear growth throughout the first 5 years of life among children from low-income and middle-income countries.Methods We analysed 87 cross-sectional Demographic and Health Surveys and Multiple Cluster Indicator Surveys (2010–2019). Growth was expressed as height-for-age z-scores (HAZ) based on the 2006 WHO Growth Standards. Sex-specific means were estimated for each country and results were pooled through random-effects meta-analysis for all children and by 12-month age groups. Using linear regression, we assessed the association between sex differences in HAZ and gross domestic product as a proxy for national economic development.Results Boys presented lower mean HAZ than girls in the first 30 months. Sex differences were mostly absent between 30 and 45 months, and in several countries, girls had lower HAZ at ages over 45 months. The pooled sex difference (boys minus girls) for the whole sample was −0.10 (95% CI −0.12 to −0.08). The difference was −0.17 (95% CI −0.20 to −0.14) at 0–11 months and −0.22 (95% CI −0.25 to −0.19) at 12–23 months. This was followed by a narrowing of the sex gap to −0.10 (95% CI −0.13 to −0.07) and −0.04 (95% CI −0.07 to −0.01) among children aged 24–35 and 36–47 months, respectively. At 48–59 months, there was evidence of female disadvantage; the mean height-for-age of boys was 0.02 (95% CI 0.00 to 0.05) SDs higher than for girls. Ecological analyses showed that in all age groups, male disadvantage decreased with increasing national income, and this was no longer present for the 4-year-old children, particularly in wealthier countries.Conclusion Male disadvantage in linear growth is most evident in the first years, but by the age of 4 years, the sex gap has mostly disappeared, and in some countries, the gap has been reversed.